Skill in ancient ethics the legacy of China, Greece and Rome - Angier, Tom 1970-; Raphals, Lisa 1951- (Bloomsbury Academic, 2022)
"This collection illustrates the centrality of skill within ancient ethics, including ancient Chinese ethics, showing how skill or techne has been a touchstone from the beginning of philosophical thought. Covering Socrates' search for expertise in virtue, the Republic's 'craft of justice', Aristotle's delineation of the politike techne and the Stoics' 'art of life'. Divided into four sections on Plato, Aristotle, the Stoics and Chinese ethics, it brings together world-leading philosophers working across this broad topic. Yet it is not limited to traditional figures and traditions, featuring essays on the importance of skill in lesser-known philosophers, such as Carneades and Antipater, and texts, such as the Zhuangzi. In doing so, it illustrates how skill, expertise and 'know how' are important in ethics, epistemology, philosophy of mind, philosophy of action and cognitive science. This collection of specially-commissioned chapters is the first to foreground skill as central to Ancient and Chinese ethics specifically making it an essential for anyone interested in the value of cross-cultural philosophy today"--
Keywords: Ideengeschichte Anfänge-500; Kompetenz; Können; technē; Philosophy, Ancient; Techne (Philosophy); Aufsatzsammlung